From Realizable Dreams to Sustainable Reality: An Empirical Study on the Relationship between Internship Experience and Future Career Prospects among Business Students - Kule, John Baguma Muhunga; Tumuhimbise, Manasseh; Kijjambu, Frederick Nsambu; Aryatwijuka, Wilbroad; Akampurira, Sarah (Journal of Economics and Behavioral Studies, 2024)
The objective of this study is to establish the relationship between Internship Experience and Future Career Prospects among Business Students at Mbarara University of Science and Technology. Using a quantitative approach and a cross-sectional survey design, data was gathered from 100 alumni. Using an open-ended questionnaire, Mbarara University of Science and Technology business students' internship experiences and future career prospects were surveyed quantitatively. In addition, a conventional linear regression analysis was performed. The study's findings demonstrated that among the Mbarara University of Science and Technology's business students, internship experience had a strong positive and significant influence on their future career prospects. The study relates to the ongoing discussion about how business students' internship experience influences their chances for future employment.
Keywords: Internship Experience; Future Career Prospects and Business Students.